2023
DOI: 10.1097/pec.0000000000002951
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Renal Angina Index to Predict the Development of Acute Kidney Injury in Children With Sepsis Who Live in Middle-Income Countries

Abstract: Objective: The renal angina index (RAI) provides a clinically feasible and applicable tool to identify critically ill children at risk of severe acute kidney injury (AKI) in high-income countries. Our objective was to evaluate the performance of the RAI as a predictor of the development of AKI in children with sepsis in a middle-income country and its association with unfavorable outcomes.Methods: This is a retrospective cohort study in children with sepsis hospitalized in the pediatric intensive care unit (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…These results are comparable to those found in our cohort and other studies conducted worldwide, as shown in Table 6 [13,17,19,22,31,33,36,37] The presence of a positive RAI and the development of AKI increased morbidity, with a higher requirement for acute renal replacement therapy up to 2 times compared to RAI-negative cases, prolonged mechanical ventilation, and an extended stay in PICU [38,39]. These results align with ndings by Ribeiro in 2021, where a positive RAI increased the use of renal support therapy by 14% vs 1% (p 0,0001) [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are comparable to those found in our cohort and other studies conducted worldwide, as shown in Table 6 [13,17,19,22,31,33,36,37] The presence of a positive RAI and the development of AKI increased morbidity, with a higher requirement for acute renal replacement therapy up to 2 times compared to RAI-negative cases, prolonged mechanical ventilation, and an extended stay in PICU [38,39]. These results align with ndings by Ribeiro in 2021, where a positive RAI increased the use of renal support therapy by 14% vs 1% (p 0,0001) [31].…”
Section: Discussionsupporting
confidence: 92%
“…These results align with ndings by Ribeiro in 2021, where a positive RAI increased the use of renal support therapy by 14% vs 1% (p 0,0001) [31]. Similarly, Suarez in 2023 described that a positive RAI increased the need for renal support therapy up to 3 times, con rming the association of a positive RAI with worse outcomes, acting as an independent marker for a longer stay in the critical care unit and more days of mechanical ventilation [12,30,33,37]. In our study, we did not nd differences in 28-day mortality among patients who did not develop AKI, in contrast to what is reported in the literature.…”
Section: Discussionsupporting
confidence: 81%